Longitudinal changes in crystalline lens thickness and power in children aged 6-12 years old - Hashemi, Hassan (2024)
Objectives: To determine the three-year changes in crystalline lens power (LP) and thickness (LT) in children and their associated factors. Methods: Schoolchildren aged 6-12 years living in Shahroud, northeast Iran were examined in 2015 and 2018. The Bennett formula was used to calculate LP. Multiple generalized estimating equations (GEE) analysis was used for data analysis. Results: Among the 8089 examined eyes, the mean LP in Phase 1 and 2, and the three-year change were 21.61 ± 1.47D, 21.00 ± 1.42D, and -0.61 ± 0.52D, respectively. The GEE model showed that negative shifts in LP were less pronounced with increasing age (β = 0.176; p < 0.001), and were also less noticeable in hyperopes compared to emmetropes (β = 0.120; p < 0.001). The changes in LP decreased when outdoor activity increased among urban residents (β = 0.013; p = 0.039), while it increased in rural areas (β = -0.020; p = 0.047). The mean three-year change in LT was 0.002 ± 0.13 mm. Female sex and aging by one year increased the LT by 0.022 mm (P < 0.001). However, LT decreased in 6-8-year-olds, while it increased in 10-12-year-old children, both in a linear fashion. The change in LT was less in myopes than in emmetropes (β = -0.018, P-value = 0.010). Conclusion: LP decreases after three years in 6 to 12-year-old children. LT increases slightly after three years in 6 to 12-year-old children. The changes in LP and LT were associated with refractive errors, place of residence, age and gender, and outdoor activity time.